Development of the Subtle ADHD Malingering Screener. (April 2019) - Ramachandran, Sujith; Holmes, Erin R.; Rosenthal, Meagen; Banahan, Benjamin F.; Young, John; Bentley, John P.
The objective of this study was to develop a subtle self-report scale—the Subtle ADHD Malingering Screener (SAMS)—to screen for malingering among individuals reporting symptoms of attention deficit/hyperactivity disorder (ADHD). This study employed a cross-sectional experimental design with an ADHD group, a control group—comprising individuals without ADHD—and a malingering group—comprising individuals without ADHD who were instructed to feign ADHD in their responses. Factor analysis and psychometric testing were conducted to develop a final scale that could distinguish the malingering from the other groups. A 10-item, two-factor solution was obtained for the SAMS, with a sensitivity of 90.3% and specificity of 80.1%. The SAMS presents an innovative approach to help reduce overdiagnosis of ADHD and misuse of prescription stimulants. The efficient, straightforward form of the measure particularly enhances its potential application in both medical and psychosocial clinical settings.